Adverse pregnancy outcomes and risk of later allergic rhinitis—Nationwide Swedish cohort study. Issue 5 (11th March 2020) - Mitselou, Niki; Hallberg, Jenny; Stephansson, Olof; Almqvist, Catarina; Melén, Erik; Ludvigsson, Jonas F.
Abstract: Background: Perinatal conditions may be associated with future allergic disease; however, data are conflicting and incomplete for childhood allergic rhinitis (AR). The aim of this study was to examine pregnancy outcome (cesarean delivery, preterm birth, low birthweight) and offspring AR as defined by national registers. Methods: Nationwide longitudinal cohort study using prospectively recorded register data from 1 059 600 singleton livebirths born in Sweden in 2001‐2012. Cox regression adjusted for infant sex and maternal factors (age at delivery, country of birth, parity, smoking, body mass index, and asthma/pulmonary disease) estimated hazard ratios (HRs) for AR during childhood. Results: During the study period 2001‐2013, 22 386 (2.11%) children were diagnosed with AR. AR was more common in infants born through cesarean delivery (2.34%) than in those born vaginally (2.10%) (HR = 1.12; 95% confidence interval [95% CI] = 1.08‐1.16). This was equivalent to one extra case of AR in 383 children followed up in our study. AR was also associated with moderately preterm birth (≥32‐36 weeks of gestation: HR = 1.12, 95% CI = 1.04‐1.20), large for gestational age (HR = 1.05, 95% CI = 1.01‐1.10), and low (<7) 5‐minute Apgar score (HR = 1.15, 95% CI = 1.02‐1.30). Similar risk estimates were obtained when we restricted the outcome to ≥2 hospital‐based records of AR. No association was observed between very preterm birth, post‐term birth, low birthweight, or small for gestational age and AR. Conclusion: Our study indicates an association between pregnancy outcomes and childhood AR, although observed effect sizes were generally modest. Abstract :